2015
DOI: 10.1007/s00405-015-3850-z
|View full text |Cite
|
Sign up to set email alerts
|

Intratemporal facial nerve schwannoma: clinical presentation and management

Abstract: Facial nerve schwannoma is the most common facial nerve tumor, but its therapeutic strategy remains debated. The aim of this study is to analyze the facial nerve function and the hearing outcomes after surgery or wait-and-scan policy in a facial nerve schwannoma series. A monocentric retrospective review of medical charts of patients followed for an intratemporal facial nerve schwannoma between 1988 and 2013 was performed. Twenty-two patients were included. Data were extracted pertaining to the following varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…This was consistent with the previous reports. [6][7][8] Accurate diagnosis is crucial in FNs as it will completely change the treatment plan. The most common pathologies to consider in differential diagnosis are VS in case of CPA localization, salivary gland tumor in case of intraparotid localization, and paraganglioma or hemangioma in case of middle ear localization.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with the previous reports. [6][7][8] Accurate diagnosis is crucial in FNs as it will completely change the treatment plan. The most common pathologies to consider in differential diagnosis are VS in case of CPA localization, salivary gland tumor in case of intraparotid localization, and paraganglioma or hemangioma in case of middle ear localization.…”
Section: Discussionmentioning
confidence: 99%
“…20,22 The complete tumor resection remains the curative treatment for GG tumors, and its indication depends on the preoperative facial nerve function. 3 Indeed, since a FN interruption is necessary in most of the cases to achieve a complete resection, most of the authors advocate surgery when the FN function is at least HB III, 3,20,21,23 or worse. A conservative approach with dissection of the FN was possible in one schwannoma as proposed by others.…”
Section: Discussionmentioning
confidence: 99%
“…2 It is a benign, encapsulated, slow growing lesion arising from the Schwann cells, that can involve any of the different segments of the FN, the geniculate ganglion (GG) being the most frequent segment involved. 3 FN hemangiomas encompass 0.7% of petrous bone tumors 4 and they have been nowadays reclassified in the group of vascular malformations. 5 As schwannomas, hemangiomas are mainly located in the GG.…”
Section: Introductionmentioning
confidence: 99%
“…The geniculate ganglion fossa is the most common location for facial nerve neurinoma [3,4]. They have reported that facial neurinoma originating in the geniculate ganglion fossa often shows extension to the tympanic and/or labyrinthine segments and that isolated involvement of the geniculate ganglion fossa at the time of the presentation is very rare.…”
Section: Discussionmentioning
confidence: 99%